Why do I get a strange answer when I plug in x=-1.001 in this function (-1.001^6-1)/(-1.001^3+1) as x--> -1

I get 600 something, but I know I should get a small integer like -2 or something.

Guest Oct 6, 2014

#2**+16 **

I think you want to evaluate this, if I'm not mistaken....

lim (x^6 -1) / (x^3 + 1)

x → -1

Factor (x^6 -1) as (x^3 - 1) (x^3 + 1) ... so we have ....

lim [(x^3 - 1)(x^3 + 1)] /((x^3 + 1)

x → -1

Simplify by "cancelling" the (x^3 + 1) terms

lim (x^3 - 1)

x → -1

Now, take the limit

[ (-1)^3 - 1] = [-1 -1 ] = -2

CPhill
Oct 6, 2014

#1**+6 **

Your question doesn't make sense because your expression only has numbers in it. It has no letters so it cannot be a function. There is nowhere to sub x=anything in because there is no x!

This is the value of the numerical expression.

$${\frac{\left({\mathtt{\,-\,}}{{\mathtt{1.001}}}^{{\mathtt{6}}}{\mathtt{\,-\,}}{\mathtt{1}}\right)}{\left({\mathtt{\,-\,}}{{\mathtt{1.001}}}^{{\mathtt{3}}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right)}} = {\mathtt{668.003\: \!447\: \!223\: \!296\: \!296\: \!3}}$$

Melody
Oct 6, 2014

#2**+16 **

Best Answer

I think you want to evaluate this, if I'm not mistaken....

lim (x^6 -1) / (x^3 + 1)

x → -1

Factor (x^6 -1) as (x^3 - 1) (x^3 + 1) ... so we have ....

lim [(x^3 - 1)(x^3 + 1)] /((x^3 + 1)

x → -1

Simplify by "cancelling" the (x^3 + 1) terms

lim (x^3 - 1)

x → -1

Now, take the limit

[ (-1)^3 - 1] = [-1 -1 ] = -2

CPhill
Oct 6, 2014